Multi-channel electronics for secondary emission grid profile monitor of TTF linac - Reingardt-Nikoulin, P.; Gaidash, V.; Mirzojan, A.; Novikov-Borodin, A. (Вопросы атомной науки и техники, 2004)
According to theTTF beam experimental program, a measurement of the time dependence of the energy spread
within the bunch train should be done by means of a standard device for profile measurements, that is Secondary
Emission Grid (SEMG). SEMG on the high-energy TTF beam is placed in the focal plane of the magnet spectrometer. It should measure the total energy spread in the range from 0.1% up to a few percents for any single or any
group of electron bunches in the bunch train of TTF Linac. SEMG Profile measurements with new high sensitive
electronics are described. Beam results of SEMG Monitor test are given for two modifications of an electronic
preamplifier. Відповідно до експериментальної програми тестового лінійного прискорювача TTF вимір часової
залежності енергетичного розкиду прискорених електронів уздовж макроімпульсу буде зроблено за
допомогою стандартного приладу для виміру профілю пучка – багатодротової повторно-емісійної камери
(ВЕММ). ВЕММ на пучку високої енергії прискорювача TTF розташований у фокальній площині
магнітного спектрометра і буде вимірювати енергетичний розкид прискорених електронів у діапазоні від
0,1% до декількох відсотків. У роботі викладаються виміри профілю пучка повторно-емісійної
багатодротовой камерою з новою високочутливою електронікою. Результати іспитів ВЕММ на пучку
прискорювача TTF і їхнє обговорення дано для двох модифікацій електронних передпідсилювачів. В соответствии с экспериментальной программой тестового линейного ускорителя TTF измерение временной зависимости энергетического разброса ускоренных электронов вдоль макроимпульса должно производиться с помощью стандартного прибора для измерения профиля пучка – многопроволочной вторичноэмиссионной камеры (ВЭММ). ВЭММ на пучке высокой энергии ускорителя TTF расположен в фокальной
плоскости магнитного спектрометра и должен измерять энергетический разброс ускоренных электронов в
диапазоне от 0,1% до нескольких процентов. В работе излагаются измерения профиля пучка вторично-эмиссионной многопроволочной камерой с новой высокочувствительной электроникой. Результаты испытаний
ВЭММ на пучке ускорителя TTF и их обсуждение приводятся для двух модификаций электронных предусилителей.